Mūsų maloniniai kreipiniai - Jasiūnaitė, Birutė (Kalbotyra, 1998)
The present article makes an attempt to analyze Lithuanian traditional terms of endearment used in popular texts of our classical literature. The terms were found to occur in 24 various situations, especially in communication between persons of different age and sex. They show a very close connection between the language and other spheres of our ethnic culture. This is especially true for the names of birds and plants, used as terms of endearment.